The impact on the accounting information after the implementation of an integrated system of administration in the Federal Institutions of Higher Education - Oliveira Neto, Josué Viana de (2005)
This article presents a research is intended to verify theories that explain the process of implementation of an Integrated System of Administration (ISA) in an organization, analyzing the effects on the use of accounting information. The empiric work based on a case study an organization that implemented of an ISA which main objective is to produce analytical reports integrated. The found evidences support the propositions done by Walton (1993:14) which describes the integration of the information technology and the organization. The results of using the information accounting in this case study evidences the difficulty in expanding the use of this type of information when they are not obtained the success in the implementation of an ISA.